Timothy J. Motley (4 June 1965–28 March 2013) and his passion for Ethnobotany and Pacific Islands flora - Delprete, Piero G. (Phytotaxa, 2015)
Timothy Jay Motley was born June 4th, 1965, to Roy and Joan (née Schaeffer) Motley, in Paxton, Illinois, USA. He grew up on a farm in east-central Illinois, and attended Armstrong-Ellis Grade School. He entered Eastern Illinois University in Charleston, Illinois, where he completed a Bachelor of Science in 1987 and a Master of Science in Botany in 1989, having written a dissertation on Sweet Flag (Acorus calamus). In 1996 he earned a Ph.D. in Botany at the University of Hawaii, Manoa; his dissertation on evolutionary and reproductive biology of Labordia (Loganiaceae). While in Hawaii, he developed a particular interest for the Pacific islands flora and for ethnobotany, two passions that he pursued for the rest of his life. Shortly after finishing his doctorate, he worked at The New York Botanical Garden (NYBG) as Post-Doctoral Research Associate (1997−1998), Assistant Curator (1998−2004), Acting Chair (1999−2000; 2001−2002), and Project Head of Conservation Genetics in Island Systems (1998−2006) in the Lewis B. and Dorothy Cullman Program for Molecular Systematics Studies. While working for NYBG, he travelled widely in regions where his projects would take him, mostly in the South Pacific, and visited the Kingdom of Tonga, Rapa Iti, Bora Bora, Papua New Guinea, Guam, Pohnpei, Fiji, Mauritius, Reunion, Vanuatu, Philippines, Jamaica, New Zealand, New Caledonia, Hawaii, and Tahiti. In 2006, he was hired as the J. Robert Stiffler Distinguished Professor of Botany and Associate Professor in the Department of Biological Sciences, Old Dominion University, and as the Director of Science at the Norfolk Botanical Garden, Norfolk, Virginia. During this period, he continued his expeditions to study and collect plants in the South Pacific and beyond, including Ecuador, the Galapagos Archipelago, Singapore, Brunei Darussalam, Mexico, the Louisiade Archipelago, and yearly field trips to underexplored regions of China. Sadly, after suffering a sudden cardiac arrest, he passed away on March 28, 2013, at age 47, at the peak of his career, leaving his wife, young son, and numerous colleagues and friends. His numerous ongoing projects, which are currently being continued by his graduate students and colleagues around the world, assure that his scientific legacy, his loving character, and his integrity will never be forgotten.